Number of categories - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
Understanding of the number of words,type of number categories.About the number word category. Gender does not find any morphological expression in English. Lexicalization of the absolute plural form of the noun can be illustrated with the following examples .Different semantic types of the singular and the plural.